Doughty-electronegative heteroatom-induced defective MoS2 for the hydrogen evolution reaction - Xiao, Zhaohui; Luo, Shengdao; Duan, Wei; Zhang, Xu; Han, Shixing; Liu, Yipu; Yang, Liang; Lin, Shiwei (Frontiers in Chemistry, 2022)
Producing hydrogen by water electrolysis is one of the most promising green energy storage and conversion technologies for the long-term development of hydrogen energy-related technologies. MoS2 is a very promising electrocatalyst that maybe replace precious metal catalysts for hydrogen evolution reaction (HER). In this work, doughty-electronegative heteroatom defect (halogen atoms, such as chlorine, fluorine, and nitrogen) was successfully introduced to the electronic structure of MoS2 by a large-scale, green and simple ball milling strategy. The physicochemical property (morphology, crystallization, chemical composition, and electronic structure) of the doughty-electronegative heteroatoms-induced defective MoS2 (N/Cl-MoS2) were identified by SEM, TEM, Raman, XRD, and XPS. Furthermore, compared with bulk pristine MoS2, the HER activity of N/Cl-MoS2 was significantly increased, which was from 442 mV to 280 mV to reach 10 mA cm-2. The research has shown that ball milling not only effectively reduced the size of catalyst material, but also could expose more active sites, and more importantly, doughty-electronegative heteroatom introduced and optimized the electronic structure of the catalyst. Therefore, the doughty-electronegative heteroatom-induced by mechanical ball milling strategy can provide a useful reference for the large-scale production of green, efficient, and low-cost catalyst materials.